The structure formed by inverted repeats in p53 response elements determines the transactivation activity of p53 protein - Brázda, Václav; Čechová, Jana; Battistin, Michele; Coufal, Jan; Jagelská, Eva B; Raimondi, Ivan; Inga, Alberto (Biochemical and biophysical research communications, 2017)
The TP53 gene is the most frequently mutated gene in human cancer and p53 protein plays a crucial role in gene expression and cancer protection. Its role is manifested by interactions with other proteins and DNA. p53 is a transcription factor that binds to DNA response elements (REs). Due to the palindromic nature of the consensus binding site, several p53-REs have the potential to form cruciform structures. However, the influence of cruciform formation on the activity of p53-REs has not been evaluated. Therefore, we prepared sets of p53-REs with identical theoretical binding affinity in their linear state, but different probabilities to form extra helical structures, for in vitro and in vivo analyses. Then we evaluated the presence of cruciform structures when inserted into plasmid DNA and employed a yeast-based assay to measure transactivation potential of these p53-REs cloned at a chromosomal locus in isogenic strains. We show that transactivation in vivo correlated more with relative propensity of an RE to form cruciforms than to its predicted in vitro DNA binding affinity for wild type p53. Structural features of p53-REs could therefore be an important determinant of p53 transactivation function.
Keywords: mutace; Chromatin; Tumor Suppressor Protein p53; Computer Simulation; Response Elements; Transcriptional Activation; Inverted Repeat Sequences; počítačová simulace; Yeasts; kvasinky; Mutation; obrácené repetice; chromatin; responzivní elementy; nádorový supresorový protein p53; aktivace transkripce